Paraneoplastic syndromes in patients with melanoma - Dec, Michał; Arasiewicz, Hubert (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2024)
Paraneoplastic syndromes are a group of rare clinical conditions characterized by a diverse array of systemic manifestations that arise in association with malignant tumours, often due to the production of bioactive substances by the tumour or an autoimmune response to the tumour. Melanoma, a malignant skin neoplasm originating from melanocytes, has been associated with various paraneoplastic syndromes. This paper provides an overview of the key paraneoplastic syndromes observed in patients with melanoma. Paraneoplastic syndromes in melanoma can manifest with neurological, dermatological, endocrine, haematological, and rheumatological symptoms, among others. Melanoma-associated retinopathy was the most reported paraneoplastic syndrome; this entity is characterized by a spectrum of retinal abnormalities. Paraneoplastic neurological syndromes, such as paraneoplastic encephalitis and paraneoplastic cerebellar degeneration, are among the most frequently reported. The pathophysiology of paraneoplastic syndromes often involves the production of autoantibodies against neuronal or tumour antigens, immune-mediated reactions, or the release of cytokines and growth factors from the tumour. Management strategies for paraneoplastic syndromes associated with melanoma primarily focus on treating the underlying malignancy, which may lead to resolution or improvement of the paraneoplastic manifestations. Immune-modulating therapies, including corticosteroids, intravenous immunoglobulins, and plasmapheresis, may be considered in selected cases to ameliorate symptoms and suppress the autoimmune response. In conclusion, paraneoplastic syndromes in patients with melanoma are a complex and diverse group of clinical entities with a broad range of presentations. Further research is needed to enhance our understanding of the mechanisms and therapeutic options for paraneoplastic syndromes associated with melanoma.